Adolescent perspectives on gendered ideologies in physical activity within schools: Reflections on a female-focused intervention - O'Reilly, M; Talbot, A; Harrington, D (SAGE Publications, 2022)
There has been growing concern about rising physical inactivity levels in female adolescents, with schools taking some responsibility to address this. Programmes designed for and by girls are increasingly being used by developing or delivering a programme of change and consultation to improve physical activity, physical education, and sport in school. However, to build an understanding of the nuances of such interventions, and better appreciate any gendered benefits and challenges, girls’ voices need to be heard. Based on data from 16 focus groups from 8 schools participating in a female-focused intervention trial (“Girls Active”), we explored adolescent girls’ views of this type of intervention. We used reflexive organic thematic analysis to understand key issues. Four themes were developed: stereotypes; choice; empowerment and voice; and equality. Our feminist approach centralised adolescent girls’ voices, thereby recognising that physical activity is rooted in patriarchal constructions that position girls as naturally uninterested in sport and activity. We suggest gender-focused interventions can actively address stereotypes by listening to girls.